Distribuição de Cr, Ni, Cu, Cd e Pb em frações húmicas de diferentes tamanhos moleculares extraídas de amostras de água e de sedimentos do reservatório de captação de água superficial Anhumas - Araraquara/SP - Dos Santos, Ademir; Rezende, Maria Olímpia de Oliveira; Rosa, André Henrique [UNESP]; Zara, Luiz Fabrício; Rocha, Julio Cesar [UNESP] (My University, 2002)
In this work was studied the distribution of Cr, Ni, Cu, Cd and Pb in humic fractions with different molecular size. The HS were extracted from waters (AHS), surface sediments (HSSS), interface water sediment (HSIS) and bottom sediment (HSBS) collected in the Anhumas surface water collection reservoir, located in the district of Araraquara - São Paulo State - Brazil. The humic substances were extracted by procedures recommended by International Humic Substances Society (IHSS). After purification by dialysis, the humic substances were fractionated using a multistage tangential flow ultrafiltration system. The fractionation patterns of HS characterized a mass distribution relatively uniform among the fractions with different molecular sizes, with larger values in the fractions F2 (20.8%) and F4 (23.8%). Except for the ions Pb(II) and Cu(II), which presented relatively higher concentrations in the fractions F2 and F4 respectively. In general, chromium, nickel, cadmium and lead have similar distributions in the five fractions with larger and medium molecular sizes (F1 to F5). With relation to the mass distributions in the different humic substances fractions extracted from sediment samples collected at three depth, they presented 42-48% of HS in the fractions with larger molecular sizes (F1 and F2), 29-31% in the middle fractions (F3 and F4) and 13-20% in the fractions with smaller molecular sizes (F5 and F6). In general, the metallic ions presented distributions similar among the respective fractions F1 to F6. Exceptions for Pb(II) and Ni(II) in surface sediment with concentrations relatively smaller in the fractions F2 and F4 respectively.
Distribution of Cr, Ni, Cu, Cd and Pb in different molecular size of humic fractions extracted from water and sediment samples collected at Anhumas reservoir - Araraquara/SP
Keywords: Fractionation; Heavy metals; Humic substances